Partial order games - Valeria Zahoransky; Julian Gutierrez; Paul Harrenstein; Michael J. Wooldridge (Games, 2022)
We introduce a non-cooperative game model in which players' decision nodes are partially ordered by a dependence relation, which directly captures informational dependencies in the game. In saying that a decision node v is dependent on decision nodes v1,…,vk, we mean that the information available to a strategy making a choice at v is precisely the choices that were made at v1,…,vk. Although partial order games are no more expressive than extensive form games of imperfect information (we show that any partial order game can be reduced to a strategically equivalent extensive form game of imperfect information, though possibly at the cost of an exponential blowup in the size of the game), they provide a more natural and compact representation for many strategic settings of interest. After introducing the game model, we investigate the relationship to extensive form games of imperfect information, the problem of computing Nash equilibria, and conditions that enable backwards induction in this new model.
Keywords: 330; backwards induction; computational complexity; game theory; Nash equilibrium; non-cooperative games